Productivity of Traditional Agrisilviculture system in Mid-Hill Situation of Garhwal Himalaya - Bijalwan, Arvind; Sharma, C.M.; Sah, V.K.; Kediyal, V.K. (Indian Journal of Agroforestry, 2020)
The productivity of traditional agrisilviculture system was studied in the six study sites of districts Tehri Garhwal in Garhwal Himalaya. The productivity of different components of agrisivilculture system viz. trees, shrubs, herbs and agriculture crops were studied. The overall productivity in agrisilviculture system was 9039 kg ha-1 yr-1 which was 56 % higher than the sole agriculture productivity (5792 kg ha-1 yr-1). The tree productivity varied 1757 kg ha-1 yr-1 to 3775 kg ha-1 yr-1, shrub productivity 817 kg ha-1 yr-1 to 1163 kg ha-1 yr-1, herb productivity varied 1072 kg ha-1 yr-1 to 1454 kg ha-1 yr-1 under agrisilviculture system. The agriculture productivity under trees ranged 3505 kg ha-1 yr-1 to 4594 kg ha-1 yr-1 as compared to 5663 kg ha-1 yr-1 to 6747 kg ha-1 yr-1 in sole agriculture crop. The reduction in biological productivity under agrisilviculture system varied 30 to 37% as compared to sole agriculture crop. The annul productivity of grain varied from 1038 kg ha-1 yr-1 to 1328 kg ha-1 yr-1. The average Harvest Index (HI) which is a parameter to measure the grain productivity varied from 32.91 to 36.10%. The pooled productivity of different components were recorded 2891, 995, 1264, 3889 kg ha-1 yr-1 for trees, shrubs, herbs and agriculture crops which contributed 32, 11, 14 and 43% respectively in the overall productivity under agrisilviculture system. The pooled productivity was 6% higher in northern aspect as compare to southern aspect.